Культурно-історичні процеси в Північно-Західному Причорномор'ї (кінець IV-ІІІ тис. до н. е.) - Іванова, С.В. (Археологія, 2015)
Стаття присвячена реконструкції культурно-історичних процесів у Північно-Західному Причорномор’ї наприкінці IV–III тис. до н. е., в період, який співвідноситься з фіналом енеоліту та ранньою бронзовою добою. Встановлено, що інтеграційні процеси в пізньому енеоліті привели до формування в регіоні буджацької культури на основі місцевого протобуджацького горизонту. The integration processes in north-west area of the Black Sea in the Late Copper Age led to the formation of Budzhak culture based on the previous Copper Age horizon. This culture’s not arrived, but local origin is evidenced also by anthropological data. Budzhak culture was an integral part of Yamna cultural and historical community, distinguishing with its specific features which were influenced by the contacts with communities in Balkan-Carpathian and Central European areas. Replacement of European cultures determined the dynamics of interrelations in various chronological periods. Eastern direction of contacts is revealed in lesser degree. It was the north-western area of the Black Sea which was the territory of departure for Yamna (Budzhak) community to the west. The analysis of the materials does not confirm the conception according to which «Kurgan cultures» invaded from the east to the west in destructive manner, on the contrary, the migration to the new territories was gradual and peaceful. The Balkan-Carpathian variant of Yamna culture is singled out and the relations with local population reflected in the material assemblage are traced. Catacomb cultures of north-west area of the Black Sea, on the contrary, are related to the eastern (initial) territories, and only a small group of burials in the Carpathian-Prut region reflects the western contacts. Viewing the archaeological situation at the background of the climatic fluctuations allowed the author to create a new model of cultural and historic processes in South-Eastern Europe in the 4th and the 3rd millennia BC, to evaluate both migrations (as trade colonization of new territories), and adaptive capacities of the ancient population of the North-West Black Sea area, and to describe the leading role of natural resources and trade in cultural and historic processes. Интеграционные процессы в Северо-Западном Причерноморье в позднем энеолите привели к формированию буджакской культуры на основе предшествующего энеолитического горизонта. О местном, а не пришлом ее происхождении свидетельствуют и антропологические данные. Буджакская культура являлась составной частью ямной культурно-исторической общности, выделяясь специфическими чертами, на формирование которых оказали влияние контакты с общностями Балкано-Карпатского и центральноевропейского ареалов. Смена европейских культур определяла динамику взаимосвязей в разные хронологические периоды. В меньшей степени в ней проявляется восточное направление контактов. Именно Северо-Западное Причерноморье было исходной территорией, откуда ямное (буджакское) население начало движение в западном направлении. Анализ материала не подтверждает концепцию о нашествии «курганных культур» с востока на запад и его деструктивный характер: переселение на новые территории было постепенным и мирным. Выделен Балкано-Карпатский вариант ямной культуры, в материальном комплексе которого отразились связи с местным населением. Катакомбные культуры Северо-Западного Причерноморья, напротив, связаны с восточными (исходными) территориями, и лишь небольшая группа погребений в Карпато-Прутском регионе отражает западные контакты. Рассмотрение археологической ситуации на фоне климатических колебаний позволило автору создать новую корректную модель культурно-исторических процессов, имевших место в Юго-Восточной Европе в IV—III тыс. до н. э., дать оценку и миграций (как торговой колонизации новых территорий), и адаптационных возможностей древнего населения Северо-Западного Причерноморья, охарактеризовать ведущую роль природных ресурсов и торговли в культурно-исторических процессах.